Sintering effect on the superconducting properties of nano-SiC added MgB2. - Tan, K. Y.; Tan, K. L.; Tan, Kar Ban; Lim, Kean Pah; Shaari, Abdul Halim; Chen, Soo Kien (Malaysian Solid State Science and Technology Society (MASS), 2011)

(untitled)
In this work, MgB2 samples added with different weight percentages (wt%) of nano-SiC additions were synthesized by the conventional solid state method. They were sintered at 650 ºC and 850 ºC respectively, in order to study the effect of sintering temperature on their phase formation and superconducting properties. XRD spectra show relatively higher intensity of Mg2Si at lower sintering temperature while Rietveld Refinement shows severe lattice contraction at a-axis but the c-axis remains unchanged with increasing SiC additions and sintering temperatures. The transition temperature degrades with the additions level but higher sintering temperature led to more gradual decrease in Tc. At 5K, samples sintered at lower temperature shows enhanced flux pinning properties with higher Jc. However, at 20K, samples sintered at higher temperature showed improved Jc at high field (>3T) when the addition level exceeds 5 wt%.